The Relationship Between Motivation and Nurses’ Performance in the Inpatient Unit of Ananda Hospital Bekasi in 2025 - Yuliyana, Nurul Mega; Wiharto, Mulyo (Jurnal Multidisiplin Sahombu, 2025)
This study explores the relationship between motivation and the performance of nurses in the inpatient unit of Ananda Hospital Bekasi. Motivation is a crucial factor influencing how health workers deliver quality services, particularly in hospital settings where patient care requires dedication, responsibility, and professional skills. A quantitative analytic design with a cross-sectional approach was applied, allowing data on motivation and performance to be examined simultaneously. Data were collected using validated questionnaires and structured performance assessments, ensuring reliability in measuring both variables. Statistical analysis demonstrated a significant association between motivation and nurse performance, indicating that higher levels of motivation are linked with better work outcomes. These findings highlight the importance of strengthening intrinsic and extrinsic motivation through organizational support, recognition, fair rewards, and professional development opportunities. The results contribute to managerial strategies aimed at improving health service quality by fostering motivated and high-performing nursing staff.